Analysis Of The Utilization Of Digital Products (Brimo) To Increasing Customer Satisfaction And Loyalty At Pt. People's Bank Of Indonesia, Tbk. Makassar Branch - Istikasari, Dian; Pahlevi, Cepi; Rahim, Fauzi R. (Program Pascasarjana STIE Amkop Makassar, 2023)
This research aims to analyze the extent to which the use of Brimo digital products influences satisfaction and the impact on customer loyalty of PT. Bank Rakyat Indonesia Tbk Makassar Branch. This study uses a quantitative approach which intends to explain the position of the variables studied and the relationship between one variable and another. This study will explain the causal relationship between variables through hypothesis testing. Based on the results of research and discussion, the conclusion of this study is that the existence of mobile banking features is proven to increase customer satisfaction and loyalty of PT. Bank Rakyat Indonesia, Tbk Makassar Branch. For the effect of mediation, it shows that customer satisfaction can mediate the effect of mobile banking on customer loyalty significantly